Relationship Of Knowledge And Attitude Of The Mother With Exclusive Breastfeeding In The Work Area Of Public Health Kajuara - Fitriani; Haerani; Tenriwati (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2021)
Background: Exclusive breastfeeding is the first, main and best food for babies, which is natural. Breast milk contains various nutrients needed in the process of growth and development of infants. The factors that influence exclusive breastfeeding are knowledge, and attitudes of mothers. Knowledge and attitudes can be used to predict the mother's desire to provide nutrition to her baby, correct knowledge about exclusive breastfeeding will respond to the mother's attitude, and can encourage further responses, namely the act of giving exclusive breastfeeding to her baby. The purpose of the study: to determine the relationship between knowledge and attitudes of mothers with exclusive breastfeeding in the work area of â€‹â€‹the Kajuara Health Center, Bone Regency. Methods: This type of research is an analytic study with a â€œcross sectionalâ€ approach. The sample in this study amounted to 38 samples. The sampling technique in this study is by means of purposive sampling. Data analysis in this study used the chi-square test statistical test. Results: Based on the results of the analysis using the chi-square test for the relationship between knowledge and exclusive breastfeeding, a significance value of 0.002 (p < 0.05) was obtained, while for the relationship between mother's attitude and exclusive breastfeeding, a significant value of 0.004 was obtained (p < 0, 05). Conclusion: There is a relationship between knowledge and attitudes of mothers with exclusive breastfeeding in the working area of â€‹â€‹the Kajuara Health Center, Bone Regency in 2021. This research suggestion can add information and input for health workers in order to improve the quality of health services provided and it is hoped that it will also provide benefits to the community.